Empowering Farmers for Sustainable Food Security: Insights from Rural Iran - Shafieisabet, Naser; Mirvahedi, Neginsadat (The International Journal of Sociology of Agriculture and Food, 2025)
This study investigates the role of structural empowerment in promoting sustainable food security in rural south-eastern Tehran, Iran. Despite its agricultural potential, the region faces persistent challenges due to weak empowerment structures. While most previous studies have focused on psychological or gender-based empowerment, this research applies Kanter’s structural empowerment theory—initially developed for formal organisations—to rural agriculture. It examines how access to information, resources, power, and support influences food security across environmental-ecological, socio-economic, political-cultural, and infrastructural dimensions. Data from 400 farmers across 37 villages were analysed using multiple linear regression and structural equation modelling (SEM). The findings reveal significant positive impacts of structural empowerment on sustainable food security. These impacts arise from awareness, knowledge, and skills, along with training, association, and both formal and informal power. In contrast, institutionalism exhibited no statistically significant effect, highlighting the region’s formal structures’ inefficiency. These results underscore the importance of social networks, informal institutions, and collective agency in enhancing farmers’ resilience and decision-making capacity. The study advocates shifting from top-down, technocratic policies to participatory, bottom-up empowerment strategies and recommends institutional reform, education and strengthening of local associations as key steps toward improving food system sustainability. This research offers a novel contribution by localising structural empowerment theory within an underexplored rural setting, providing valuable insights for policymakers, practitioners, and scholars in agricultural development. It calls for multidimensional policy interventions that address both individual and structural factors. Future studies should investigate gender disparities, conduct cross-regional comparisons, and refine empowerment metrics to enhance the applicability and relevance of findings across contexts.